Evaluasi Pelaksanaan Percepatan Restitusi Pajak Penghasilan Bagi Wajib Pajak Orang Pribadi - Hasanah, Huswatun; Nuryanah, Siti (E-Jurnal Akuntansi; Vol 34 No 7 (2024), 2024)
Acceleration of tax refund for individual taxpayers is Indonesia government’s facility to a preliminary refund of Income Tax overpayment for Individual Taxpayers by guaranteeing the settlement process within 15 (fifteen) working days. This study aims to analyze how the accelerated income tax refund for individual taxpayers are implemented based on the four maxims principle, namely equality, certainty, convenience, and economy. The survey sample consisted of individuals with the individual taxpayer’s criteria who had submitted the2022 individual income tax return selected with a simple random sampling approach. This study uses primary data derived from the distributing questionnaire and in-depth interviews. Likert scale is used to assist in data analysis for tests conducted in this study. The results of this study indicate that the application of accelerated income tax restitution for WPOP has fulfilled the principles of equality, certainty, convenience, and economy. However, there are several things that need to be improved in terms of individual taxpayer's understanding of tax administration to accelerate income tax refunds for individual taxpayers. Keywords: Acceleration of Restitution Individual Taxpayer; Income Tax; Individual Tax Payers; Principle of Tax Collection,